Integrated QFD/DFM approach for generating product design specifications - Arumugam Vijayarani. (2008)
DFM (Design for Manufacture) Methodology is used to evaluate the design alternatives from a manufacturing cost perspective and to improve the design efficiency, before commitment to detail design. On the other hand, QFD (Quality function deployment) methodology provides a structured framework that helps in the mapping of customer requirements into specific design features through one or more matrices of expectations. The incorporation of DFM principles and methodology into the QFD process offers important benefits such as increased design efficiency and increased customer satisfaction.